Pericardial Fat is Associated with All-Cause Mortality but not Incident CVD: The Rancho Bernardo Study - Larsen, Britta A. (Atherosclerosis, 2015)
OBJECTIVE: Pericardial and intra-thoracic fat are associated with prevalent cardiovascular disease (CVD) and CVD risk factors. However, it is unclear if these fat depots predict incident CVD events and/or all-cause mortality. We examined prospective associations between areas of pericardial and intra-thoracic fat and incident CVD and mortality over a 12-year follow-up in a subset of participants without baseline clinical CVD from the Rancho Bernardo Study (RBS). METHODS: Participants were 343 community-dwelling older adults (mean baseline age=67) who completed a clinic visit in 2001–02, including a computed tomography scan of the chest. Incident CVD and mortality were recorded through January 2013. RESULTS: Over a 12.6-year median follow-up, there were 60 incident CVD events and 49 deaths. Pericardial fat was associated with all-cause mortality, such that each standard deviation increment predicted a 34% higher chance of death after adjusting for demographics, lifestyle factors, comorbidities, and visceral fat (95% CI=1.01–1.78). When categorized by tertile, those in the middle tertile of pericardial fat showed no increased risk of mortality, while those in the highest tertile had 2.6 times the risk (95% CI=1.10–5.97) compared to the lowest tertile. There was a marginal association between intra-thoracic fat and mortality (p=0.06). Neither pericardial nor intra-thoracic fat was significantly associated with incident CVD. There were no significant interactions by sex. CONCLUSIONS: Higher pericardial, but not intra-thoracic, fat was associated with earlier all-cause mortality in older adults over a 12-year follow-up. This association was primarily driven by a higher mortality rate in those in the highest tertile of pericardial fat.